CNS Macrophages Control Neurovascular Development via CD95L - Si Chen (Cell Reports, 2017)
The development of neurons and vessels shares striking anatomical and molecular features, and it is presumably orchestrated by an overlapping repertoire of extracellular signals. CNS macrophages have been implicated in various developmental functions, including the morphogenesis of neurons and vessels. However, whether CNS macrophages can coordinately influence neurovascular development and the identity of the signals involved therein is unclear. Here, we demonstrate that activity of the cell surface receptor CD95 regulates neuronal and vascular morphogenesis in the post-natal brain and retina. Furthermore, we identify CNS macrophages as the main source of CD95L, and macrophage-specific deletion thereof reduces both neurovascular complexity and synaptic activity in the brain. CD95L-induced neuronal and vascular growth is mediated through src-family kinase (SFK) and PI3K signaling. Together, our study highlights a coordinated neurovascular development instructed by CNS macrophage-derived CD95L, and it underlines the importance of macrophages for the establishment of the neurovascular network during CNS development.